The Impact of Relationship Education on the Couple Relationship: A Grounded Theory of Intentionality and Awareness. Issue 2 (3rd April 2019) - Novak, Joshua R.; Whiting, Jason B.; Brown, Matthew D.; Harris, Steven M.
ABSTRACT: Research on relationship education (RE) programs generally shows their effectiveness, but it is important to understand what the mechanisms of change are, how they occur within programs, and what participants experience. The purpose of this study was to explore couples' perceptions of the key components of their experience as participants of a Prep-based RE program. Research questions included: How do couples describe their experience of taking an 8-hour relationship education class? What elements had the biggest impact on their relationship? How has their relationship changed as a result of participation? Interview data from 39 married and cohabitating couples who participated in RE were analyzed using grounded theory methods. Six categories emerged from the analytic process, resulting in a model that provided explanatory detail of a typical RE program experience and its impact on the participants. These categories were: intentionality and awareness, context, relationship, workshop, impact (of RE), and couple interview. Couples described these categories as developing in a relatively chronological order, with Intentionality and Awareness being a central category that cut across the process and helped explain the impact of the program on the couple relationship. Implications for research, program development, and program facilitators providing RE are discussed.